Institutional reform and pockets of effectiveness in the Mozambique gas sector - José Jaime Macuane; Lars Buur; Padil Salimo (Roskilde University, Department of Social Sciences and Business, Socio-Economic Research Centre (SECO), 2022)
Given the increasing importance of gas in the Mozambican economy, the success of institutional reforms is key to the country's economic prospects of benefiting positively from the expected gas bonanza. In this paper we analyze the performance of the new institutional reforms (NIA) in Mozambique, specifically the replication of the so-called Norwegian Model of oil governance, and the conditions of the emergence and persistence of pockets of effectiveness in the sector, taking into account the political context, especially the regime survival. Our analytical framework is based on political settlement analysis and pockets of effectiveness (PoEs) theory. Based on two case studies from the sector - the National Petroleum Institute and the Tax Authority (the Extractive Industries Tax Unit) - we analyze the performance of the institutional reforms and the conditions for the emergence and persistence of PoEs in the gas sector, as one of the strategies for regime survival. From our analysis we conclude that, whilst external dependence on development aid and foreign direct investment is important, internal political dynamics, particularly intra-ruling-elite competition, explain the performance of the institutional reforms and the emergence and persistence of PoEs in the sector as a regime survival strategy.
Keywords: 330; Gaswirtschaft; Erdölindustrie; Institutioneller Wandel; Performance-Messung; Branchenentwicklung; Mosambik